Design and application of the sports internet as a teaching platform - Jiang, D.; Peijun, Z.; Chunqing, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The internet is a basic example of a modern information dissemination technique that displays elements of variety, internationalism and innovation and it is now closely related to the development of sport and sports education within this informative social environment of the 21the century. The purpose of this paper is to demonstrate the importance of internet-based teaching methods, and to provide a successful platform for internet-based sports teaching.